Childhood MMR Vaccination Effectiveness Against Rubella: A Longitudinal Cohort Study. (May 2022) - Geier, David A.; Geier, Mark R.
The vaccine effectiveness (VE) of childhood measles-mumps-rubella (MMR) vaccine to reduce childhood rubella infections in the US during the 1990s/2000s was undertaken in a retrospective longitudinal cohort study. SAS and StatsDirect software were utilized to examine non-identifiable linked eligibility and claim healthcare records prospectively generated from the Florida Medicaid system in the Independent Healthcare Research Database (IHRD). A total of 33 839 children received a single MMR vaccination (vaccinated) and 44 154 children never received a rubella-containing vaccine (unvaccinated) were continuously eligible from 1990 to 2009 for Florida Medicaid within the first 10 years following birth. Cox proportional hazards models determined VE against diagnosed rubella (ICD-9 code: 056.xx). Children receiving MMR were at significantly reduced risk of rubella in unadjusted (VE = 80.7%, 95% confidence interval = 73.7%-85.8%) and adjusted (VE = 78.6%, 95% confidence interval = 70.8%-84.3%) models as compared to unvaccinated children. Between 1991 and 2009, in the combined vaccinated-unvaccinated cohort examined on a yearly basis, a significant inverse correlation between increasing MMR vaccine population coverage and a decreasing incidence rate of diagnosed rubella was observed. This first large-scale population epidemiological study supports the routine use childhood MMR vaccination to significantly reduce childhood rubella infections and also supports its ability to induce "herd immunity." This study, coupled with a recently published epidemiological study showing childhood MMR vaccination significantly reduced measles infections, provide powerful epidemiological evidence strongly supporting MMR vaccination as an effective tool to improve public health.